Pengaruh Penggunaan Jamur Kuping (Auricularia Auricula) Sebagai Bahan Pensubstitusi Daging Sapi Terhadap Komposisi Proksimat Dan Daya Terima Bakso - SULISTIYANI, Sulistiyani; , Pramudya Kurnia, STP, M.Agr; , Eni Purwani, S.Si., M.Si (2015)
Introducton : Meatballs is the homogeny mixing of meat, tapioca flour, and ingredients. The other alternative protein resource is fungus. Fungus is considered as a substituted material because it is safe to comsumed and there is not cholesterol, besides of that it is a vegetable protein reseurce the cheaper. Purpose : The purpose of this research was investigate the proximate composition and acceptance level of meatball that substituted with fungus. Method : Completely randomize designed was used with variation of substitution level, were 0%, 10%, 20%, and 30%. The data were analyzed using one way anova and followed by DMRT (Duncan Multiple Range Test) at a level 95%. Result : The highest of water on fungus substitution 0% (control) is 78,36%. The highest of dust on fungus substitution 10% is 1,96%. The highest of protein on fungus substitution 0% (control) is 10,26%. The highest of fat on fungus substitution 10% and 20% is 2,33%, with the best perception is fungus substitution 10% saying happines (5,60%). Conclusion : The result showed that there was effects of fungus substitution (p<0,05) to the degree of water, dust, fat, and protein of meatballs. There was not effects of fungus substitution (p>0,05) to the degree of carbohidrat meatballs. There was effects fungus substitution in making meatballs to its acceptance. Suggest : It is good using fungus 10% as substituted material in meatball making.